Critical values notification: A nationwide survey of practices among clinical laboratories across Nigeria - Lucius C. Imoh; Idris Y. Mohammed; Ifeyinwa D. Nnakenyi; Ephraim U. Egbuagha; Tomisin M. Adaja; Chinelo P. Onyenekwu (AOSIS, 2023)
Background: Critical value notification (CVN) entails notifying doctors or other laboratory users of aberrant laboratory results that threaten the patient's life and of any values for which reporting delays could negatively impact the patient's health. Critical value notification practices in clinical laboratories in Nigeria and sub-Saharan Africa are largely unknown. Objective: We conducted a nationwide survey to obtain baseline information on CVN practice by Nigeria's laboratories. Methods: This cross-sectional study was conducted among purposively selected secondary- and tertiary-tier, public and private clinical laboratories across northern and southern Nigeria between October 2015 and December 2015. Consenting senior laboratory staff completed and returned a structured questionnaire, that gathered data on respondents' demographics, designations, and institutional characteristics and practices regarding CVN. Results: One hundred and thirty-four laboratories responded to the questionnaires. Only 69 (51.5 %) laboratories practised CVN; only 23 (33.3%) had existing written policies guiding the practice. Most (43; 62.3%) laboratories use similar critical values (CVs) for adult and paediatric populations. Most laboratories (27; 39.1%) obtained their CVs by combining published literature and local opinions from stakeholders. Physical dispatch (42; 60.9%) followed by telephone calls (38; 55.1%) were the most common means of notification. Private laboratories, compared with public hospital laboratories, were likelier to have separate paediatric CV lists (p = 0.019) and practise telephone notifications (p  0.001). Conclusion: Critical value notification practices vary and are often suboptimal in many clinical laboratories in Nigeria, which is exacerbated by the absence of guiding policies and national recommendations for post-analytical procedures. What this study adds: This study provides baseline information on CVN practice by Nigeria's laboratories. The study explores the causes of practice variations that can serve as a foundation for enhancing critical reporting and post-analytical services, particularly in clinical laboratories in sub-Saharan Africa.